How to win in FIFA World Cup Qatar 2022? A study on the configurations of technical and tactical indicators based on fuzzy-set qualitative comparative analysis - Yan, Weihua; Li, Shiyue; Wang, Di; Yuan, Bo; Zeng, Haocheng; Ren, Dingmeng (Frontiers in Psychology, 2024)
The FIFA World Cup, which represents the highest level in football, is regarded as a showcase to unfold the development trends of modern football, thus arousing great interest among researchers. However, most of the previous research designs studied the simple linear correlation between technical indicators and game outcomes, which may overlook the complex causalities in football performance. The aim of current study was to introduce a new method to examine winning patterns emerging from Qatar 2022 through a configurational lens. To this end, fuzzy-set qualitative comparative analysis (fsQCA) was conducted using 98 samples (n = 98) out of 49 Qatar 2022 matches discriminating winning and losing teams in regular time (group stage) and in 30 min of extra time (knockout stage). Then, we selected seven variables as our causal conditions, namely, shots on target, possession, defensive line breaks, crosses, receptions in the final third, forced turnovers, and direct pressures. Necessity analysis and sufficiency analysis of configurations were conducted according to fsQCA requirements. The fsQCA operation showed that no individual causal condition is necessary to winning a game and four configurations were derived from the QCA results and these combinations of conditions fall into three typologies of play style: a possession play style, direct play style, and all-round play style. The results confirmed the fact that football is a complex system and suggested that a winning outcome is often produced by combinations of multiple factors. The findings of the current study contribute to the literature by introducing the configurations of various technical and tactical indicators that could raise the possibility of winning and can be used by practitioners working within the fields of player development, coaching, and match preparation.